AI-BASED DECISION MAKING IN MACRO AND MICROECONOMICS: TOWARD OPTIMAL EFFICIENCY - Loso Judijanto; Bahrun Thalib; Haryanto; Al-Amin (CV. Adiba Aisha Amira, 2024)
In the last decade, Artificial Intelligence (AI) has moved from being a futuristic concept to a critical component of economic decision-making. The use of AI has been extended to various aspects of the economy, ranging from strategic decision-making at the firm level to macroeconomic policy at the government level. This study aims to examine the impact of AI on decision-making in macro and microeconomics, and understand how optimal efficiency can be achieved through the implementation of this technology. The study conducted in this research utilizes the literature research method. The results of this study show that AI has the potential to increase economic growth due to increased productivity and operational efficiency. At the macro level, AI contributes to more accurate policy planning and efficient resource management. At the micro level, AI supports businesses in gaining competitive advantage through supply chain optimization, personalization of service offerings, and better customer data management. However, the findings also emphasize the importance of addressing ethical, privacy, and accessibility challenges to ensure that the benefits of AI are widely and equitably enjoyed.